The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s40820-021-00695-3
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency Wastewater Purification System Based on Coupled Photoelectric–Catalytic Action Provided by Triboelectric Nanogenerator

Abstract: It is of great importance to explore a creative route to improve the degradation efficiency of organic pollutants in wastewater. Herein, we construct a unique hybrid system by combining self-powered triboelectric nanogenerator (TENG) with carbon dots-TiO2 sheets doped three-dimensional graphene oxide photocatalyst (3DGA@CDs-TNs), which can significantly enhance the degradation efficiency of brilliant green (BG) and direct blue 5B (DB) owing to the powerful interaction of TENG and 3DGA@CDs-TNs photocatalyst. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…Shen et al reported a TENG based on a disc structure combined with photoelectric catalysis (Figure di). This self-powered hybrid system significantly improved the removal efficiency of brilliant green and direct blue 5B (Figure dii) . In addition, due to photoelectrical coupling, a polytetrafluoroethylene-Al-based TENG increased the degradation rate of MO by 49% in 120 min .…”
Section: Self-powered Electrochemical Systems For Wastewater Treatmentmentioning
confidence: 92%
See 2 more Smart Citations
“…Shen et al reported a TENG based on a disc structure combined with photoelectric catalysis (Figure di). This self-powered hybrid system significantly improved the removal efficiency of brilliant green and direct blue 5B (Figure dii) . In addition, due to photoelectrical coupling, a polytetrafluoroethylene-Al-based TENG increased the degradation rate of MO by 49% in 120 min .…”
Section: Self-powered Electrochemical Systems For Wastewater Treatmentmentioning
confidence: 92%
“…TENG-photo/electric coupling improves the separation of photoinduced electron–hole pairs and further increases the efficiency of the photocatalyst. Researchers have used TENG-photo/electric coupling applications in wastewater treatment to treat municipal wastewater (e.g., antibiotics) and industrial wastewater (e.g., dye). , Table presents various TENG-photo/electric coupling applications in wastewater treatment, which activate free radical species to enhance the oxidation of a wide range of contaminants and increase the extent of this enhancement under different conditions. This combination of mechanical and solar energy is inspiring for the design of environmentally friendly photoelectric catalysis systems for wastewater treatment.…”
Section: Self-powered Electrochemical Systems For Wastewater Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Therefore, there is a great demand for the development of selfpowered technologies with renewable, portable, and sustainable sources and intelligent manufacturing. [10][11][12][13][14][15][16] As a good alternative, piezoelectric nanogenerators (PENGs) with selfpowered operation have received growing attention, which is attributed to their ability to harvest energy under external mechanical stimulation from human motion or the surrounding environment. [17][18][19][20] Furthermore, additive manufacturing technologies with exibility and rapid prototyping capability have been successfully utilized for the fabrication of wearable PENGs in recent years, which can benet from their excellent ability to be rapidly molded with facility, scalability, and cost-effectivity to produce structures of any design or shape.…”
Section: Introductionmentioning
confidence: 99%
“…To resolve them, this has led to extensive research on contaminated water purification as well as hydrolysis of hydrogen production [ 1 5 ], which often refers to the advanced functional nanomaterials. Catalytic membrane has both filtration and catalytic properties, and is one of the potential materials for sewage treatment and hydrogen production [ 2 4 ]. Among them, material scientists have paid the much attention to the graphene oxide (GO) membranes because of their high structure stability, exceptional water permeation and molecular sieving properties [ 5 ].…”
Section: Introductionmentioning
confidence: 99%